2022
DOI: 10.5089/9798400204364.001
|View full text |Cite
|
Sign up to set email alerts
|

Trade and the COVID-19 Pandemic: Lessons from French Firms

Abstract: IMF Working Papers describe research in progress by the author(s) and are published to elicit comments and to encourage debate. The views expressed in IMF Working Papers are those of the author(s) and do not necessarily represent the views of the IMF, its Executive Board, or IMF management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…This explains that COVID-19 pandemic as an event does not have an impact on global trade if we consider the pre-COVID-19 and post-COVID-19 trades as of 2022. This also explains the rebound in trade as presented by Brussevich et al (2022). We also analyzed the impact of the Russia-Ukraine War (equations 7,8 and 9) and found that trade flow, Export, and Import are positive despite the war.…”
Section: Discussion and Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…This explains that COVID-19 pandemic as an event does not have an impact on global trade if we consider the pre-COVID-19 and post-COVID-19 trades as of 2022. This also explains the rebound in trade as presented by Brussevich et al (2022). We also analyzed the impact of the Russia-Ukraine War (equations 7,8 and 9) and found that trade flow, Export, and Import are positive despite the war.…”
Section: Discussion and Resultsmentioning
confidence: 76%
“…Brussevich et al (2022) suggested that the initial collapse in trade flows and the subsequent recovery after the initial phase of Covid-19 in 2020 was demand-driven. Citing WTO, Brussevich et al (2022) identified several factors contributing to the rebound-(i) proactive fiscal and monetary policies combined with trade policy restraint in protecting supply chains (ii) technological innovation which facilitated remote working (iii) shift in consumer demand to online based businesses or ecommerce. Jiang et al (2022) studied the post-Covid economic recovery of China by constructing a macroeconomic resilience index.…”
Section: Key Themes and Findings In Recent Workmentioning
confidence: 99%
“…where the subscript i indicates the firm, p indicates the product at the 6-digit level of the CN classification, c is the country of origin or destination and t is time (year & month). Following Brussevich et al (2022), since a non-negligible part of the adjustment took place through the extensive and sub-extensive margins, the dependent variable is the monthly year-on-year mid-point growth rate, defined as follows:…”
Section: Methodsmentioning
confidence: 99%
“…To proxy the severity of the pandemic shock, I employ the data of the Oxford Covid-19 Government Response Tracker (OxCGRT), which is described in Hale et al (2021) and includes a large number of Covid-19 related indicators for nearly all countries in the world. Following Brussevich, Papageorgiou, and Wibaux (2022), I focus in particular on two indices: the (monthly average) stringency index, which is a synthetic measure of the stringency of lockdowns implemented by governments at each point in time, and the monthly death rate of Covid-19 by country.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation